Attention to beds in natural scenes by observers with insomnia symptoms. (May 2017) - Beattie, Louise; Bindemann, Markus; Kyle, Simon D.; Biello, Stephany M.
Abstract: Attention biases to sleep-related stimuli are held to play a key role in the development and maintenance of insomnia, but such biases have only been shown with controlled visual displays. This study investigated whether observers with insomnia symptoms allocate attention to sleep-related items in natural scenes, by recording eye movements during free-viewing of bedrooms. Participants with insomnia symptoms and normal sleepers were matched in their visual exploration of these scenes, and there was no evidence that the attention of those with insomnia symptoms was captured more quickly by sleep-related stimuli than that of normal sleepers. However, the insomnia group fixated bed regions on more trials and, once fixated on a bed, also remained there for longer. These findings indicate that sleep stimuli are particularly effective in retaining visual attention in complex natural scenes. Highlights: People with insomnia symptoms exhibit attention biases to sleep-related items. These biases have been observed with highly controlled stimuli or contrived scenes. This study investigates such biases during the viewing of beds in natural scenes. People with insomnia symptoms demonstrated attention retention but not capture by beds. A sleep threat interpretation of these findings is proposed speculatively.